Pengaruh Lingkungan Keluarga, Motivasi Belajar Dan Disiplin Belajar Terhadap Prestasi Belajar Mata Pelajaran Ekonomi Siswa Slta Di Kecamatan Panti - Panaehan Panaehan; bustari muchtar (Program Magister Pendidikan Ekonomi (S2), 2014)
This study aims to analyze (1) the influence of family environment on learning achievement (2) the influence of family environment and motivation toward learning achievement (3) the influence of family environment, learning motivation and discipline learned in student performance on economic subjects high school in Panti Subdistrict. This research is associative descriptive. The population of this study were all high school students enrolled in Panti Subdistrict on the academic year 2013/2014, totaling 854 people. The sampling technique with proportional random sampling with a sample size of 90 people. The technique of data analysis is descriptive analysis and inductive analysis, namely: normality test, homogeneity. The data were processed by using path analysis. The results showed that (1) there is a significant relationship between family environment on student motivation on economic subjects Panti high school students in Subdistrict, (2) there is a significant relationship between family environment and motivation to learn discipline on economic subjects high school students in Panti Subdistrict, and (3) a significant difference between family environment, learning motivation and discipline of learning on student achievement on economic subjects high school student in Panti Subdistrict.